Tissue distribution of quiescin Q6/sulfhydryl oxidase (QSOX) in developing mouse - Portes, Kelly F.; Ikegami, Cecília M.; Getz, Joselito; Martins, Ana P.; de Noronha, Lucia; Zischler, Luciana F.; Klassen, Giseli; Camargo, Anamaria A.; Zanata, Silvio M.; Bevilacqua, Estela; Nakao, Lia S. (Journal of molecular histology, 2008)
Quiescin Q6/sulfhydryl oxidases (QSOX) are revisited thiol oxidases considered to be involved in the oxidative protein folding, cell cycle control and extracellular matrix remodeling. They contain thioredoxin domains and introduce disulfide bonds into proteins and peptides, with the concomitant hydrogen peroxide formation, likely altering the redox environment. Since it is known that several developmental processes are regulated by the redox state, here we assessed if QSOX could have a role during mouse fetal development. For this purpose, an anti-recombinant mouse QSOX antibody was produced and characterized. In E 13.5 , E 16.5 fetal tissues, QSOX immunostaining was confined to mesoderm- and ectoderm-derived tissues, while in P1 neonatal tissues it was slightly extended to some endoderm-derived tissues. QSOX expression, particularly by epithelial tissues, seemed to be developmentally-regulated, increasing with tissue maturation. QSOX was observed in loose connective tissues in all stages analyzed, intra and possibly extracellularly, in agreement with its putative role in oxidative folding and extracellular matrix remodeling. In conclusion, QSOX is expressed in several tissues during mouse development, but preferentially in those derived from mesoderm and ectoderm, suggesting it could be of relevance during developmental processes.